2018
DOI: 10.5223/pghn.2018.21.4.264
|View full text |Cite
|
Sign up to set email alerts
|

Initial Diagnosis of Functional Gastrointestinal Disorders in Children Increases a Chance for Resolution of Symptoms

Abstract: PurposeThe aim of this study was to describe functional gastrointestinal disorders (FGID) presented in a tertiary medical center, characteristics of patients and results of the diagnostic work-up together with an outcome during the follow up.MethodsThis was a retrospective, single center, observational study including all patients who were diagnosed with FGID based on Rome III criteria from January to December 2015 in tertiary medical center.ResultsOverall 294 children were included (mean age, 8.9 years [range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 18 publications
(22 reference statements)
0
21
0
2
Order By: Relevance
“…The diagnosis of pediatric FC is based on a “positive” approach that avoids unnecessary tests to rule out an organic cause 1213. Scarpato et al8 reported that 42% of pediatricians considered FC a diagnosis of exclusion that was reached after a thorough diagnostic evaluation for other etiologies.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of pediatric FC is based on a “positive” approach that avoids unnecessary tests to rule out an organic cause 1213. Scarpato et al8 reported that 42% of pediatricians considered FC a diagnosis of exclusion that was reached after a thorough diagnostic evaluation for other etiologies.…”
Section: Discussionmentioning
confidence: 99%
“…2.2. Имеются отдельные сообщения, в которых функциональная тошнота и функциональная рвота встречались у 0,7% детей в возрасте 8-18 лет, функциональная тошнота у 3,4% [4][5][6][7].…”
Section: эпидемиологияunclassified
“…10,11 A recent study also suggested that diagnosing an FGID at the first visit was the only significant prognostic factor associated with symptom resolution. 12 Thus, early and adequate diagnoses are essential for appropriate treatment in patients with FC, ultimately leading to better outcomes in these patients.…”
mentioning
confidence: 99%
“…It is noteworthy that this study investigated the Rome IV questionnaires in an unselected outpatient population. Few studies have evaluated the prevalence of FC using the Rome criteria and most of them were conducted in secondary and tertiary hospitals, [12][13][14] while the majority of children suffering from constipation are present and managed in a primary care setting. Moreover, the diagnosis of FC was made not only based on a questionnaire, but also included a physical examination in this study.…”
mentioning
confidence: 99%